2003
DOI: 10.1590/s1413-86702003000400004
|View full text |Cite
|
Sign up to set email alerts
|

Use of rhu-GM-CSF in pulmonary tuberculosis patients: results of a randomized clinical trial

Abstract: It has been postulated that deficient or incomplete clinical and/or microbiological response to tuberculosis treatment is associated with cell-mediated immunological dysfunction involving monocytes and macrophages. A phase 2 safety trial was conducted by treating patients with either recombinant human granulocyte-macrophage colony-stimulating factor (rhu-GM-CSF) or a placebo, both in combination with anti-tuberculosis chemotherapy. Thirty-one patients with documented pulmonary tuberculosis were treated with ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 23 publications
(21 reference statements)
1
30
0
Order By: Relevance
“…Recombinant human GM-CSF has been used in humans to improve the immunological function of patients with various infectious diseases. A recent trial of GM-CSF co-delivery with antibiotic chemotherapy of patients with active tuberculosis revealed that, with the exception of one patient with primary tuberculosis resistance, all patients in the GM-CSF group were culture negative at six months [33]. Our data indicate that delivery of GM-CSF via BCG does not significantly alter the in vivo replication kinetics of parental BCG in mice (Fig.…”
Section: Discussionmentioning
confidence: 47%
“…Recombinant human GM-CSF has been used in humans to improve the immunological function of patients with various infectious diseases. A recent trial of GM-CSF co-delivery with antibiotic chemotherapy of patients with active tuberculosis revealed that, with the exception of one patient with primary tuberculosis resistance, all patients in the GM-CSF group were culture negative at six months [33]. Our data indicate that delivery of GM-CSF via BCG does not significantly alter the in vivo replication kinetics of parental BCG in mice (Fig.…”
Section: Discussionmentioning
confidence: 47%
“…Thus far, one phase-II controlled clinical trial of GM-CSF used in conjunction with chemotherapy has been performed. Results showed no major differences between the treatment and control groups, although faster clearance of acidfast bacilli in sputum was observed in the GM-CSF treatment group [84].…”
Section: Gm-csfmentioning
confidence: 80%
“…In humans, however, the use of tumor cells engineered to over-express GM-CSF have extensively been tested in clinical trials, and for the most part the regime is well tolerated (44). Further, recombinant human GM-CSF has been tested in combination with rifampin/isoniazid to treat patients with active tuberculosis with no adverse effects (45). Thus the capacity to deliver transiently low levels of immunostimulatory cytokines via BCG may be advantageous in invoking protective immune responses without negatively influencing pathology.…”
Section: Discussionmentioning
confidence: 99%
“…Murine and human GM-CSF display limited biological cross-reactivity (49), which suggests modification of the recombinant strain would be required for use in humans. However the potent activity of human GM-CSF on APC function (44), coupled with the favorable safety profile of studies employing human GM-CSF in clinical trials (44,45), suggests further study of this vaccine as a candidate to protect against tuberculosis in human populations is warranted. …”
Section: Discussionmentioning
confidence: 99%